PENERAPAN MODEL PEMBELAJARAN EXPLICIT INSTRUCTION BERBANTUAN CD INTERAKTIF UNTUK MENINGKATKAN AKTIFITAS DAN HASIL BELAJAR SISWA KELAS X MULTIMEDIA DALAM PEMBELAJARAN AUDIO DIGITAL DI SMK TI BALI GLOBAL SINGARAJA - I Wayan Ardi Marta Eka Yasa (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
This study aims to determine the extent to which the application of Explicit Instruction learning models Interactive CD assisted activity and can enhance students' learning in class X Multimedia digital audio on the basic competence to design and editing digital audio. The method used is a Classroom Action Research (PTK) on class X Multimedia in SMK TI Bali Global Singaraja on academic year 2011/2012. The instrument used was a formative tests, observation sheets, and questionnaires. Data obtained from this study that the average student in the cycle I is the lowest value of 75.65 with a highest value of 63 and 88, while studying classical completeness percentage 82.61%. In the second cycle the average student is 81.70 and the lowest 72 the highest value 95, while studying classical completeness percentage of students in the second cycle is 100%. In addition to improved student learning outcomes, the study also obtained the result of increased student learning activities is evident from an average increase of 16.1 student learning activities in cycle I to 19.3 in the second cycle are classified as very active. Based on the students questionnaire responses showed that application of the Explicit Instruction assisted learning model assisted Interactive CD has received a very positive response from students. Action hypothesis in this study received, thus the application of Explicit Instruction learning models assisted interactive CD can enhance the activity and student learning outcomes in teaching digital audio.Keywords: Learning Model, Explicit Instruction, Interactive CD, Classroom Action Research, Learning Activities, Learning Outcomes, Student Response.